Evaluasi Kinerja Komite Madrasah Dalam Peningkatan Mutu Pendidikan - Aisyah, Aisyah; Ali Buto, Zulfikar; Nazar, M (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
This study evaluates the performance of the Madrasah Committee in improving the quality of education, focusing on its roles in planning, implementing, and monitoring programs. Using a qualitative descriptive method, the study collected data through interviews, observations, and document analysis at a single madrasah in Aceh. The findings reveal that the committee effectively supports madrasah development by engaging in resource mobilization, improving teacher competencies through training programs, and fostering community participation. However, challenges such as limited financial resources and ineffective communication among stakeholders hinder optimal performance. Recommendations include enhancing committee training, increasing collaboration with external partners, and establishing clear communication frameworks. The study highlights the importance of the Madrasah Committee as a strategic partner in creating an inclusive and high-quality education system. Future research should consider a comparative analysis across different madrasahs to provide a broader understanding of the committee’s impact.